S139 Cough responses to tussive agents in health and disease. (2nd December 2011) - Khalid, S; Dockry, R; Holt, K; Sumner, H; Valdramidou, D; Birrell, M A; Belvisi, M G; Woodcock, A; Smith, J A
Abstract : Introduction: Capsaicin or citric acid cough challenges have been used as an objective measure of cough reflex sensitivity for many decades. It remains unclear how the response to these agents differs in different diseases and how the response to one cough challenge agent differs from that to another. Prostaglandin E2 is known to result in cough when given as an inhalational agent, but has not been used as inhalational cough challenge agent. Objectives: To assess the ability of individual challenges and combined challenge responses to discriminate between diagnostic groups and healthy volunteers. Methods: We studied 102 subjects, median age 60.0 years (IQR 51.0–65.0) and 50% female (healthy volunteers n=21, healthy smokers n= 20, COPD n=18, asthma n=22 and chronic cough n=21). A doubling-dose, single inhalation method was used to measure the concentration of capsaicin (CAP), citric acid (CA) and prostaglandin E2 (PGE2) evoking at least 5 coughs (C5) within 15 s of administration, performed at weekly intervals. The operator was blinded to the challenge agent and each challenge contained 3 randomly interspersed placebo inhalations (saline). Data was analysed by multinomial logistic regression with healthy volunteers used as the reference category. Results: Smokers (p=0.03) and COPD patients (p=0.003) had a significantly higher PGE2 logC5 than healthy volunteers. CA logC5 however was significantly lower in asthma (p=0.013), and chronic cough (p=0.001) compared with healthy volunteers. CAP logC5 was also significantly lower in chronic cough (p<0.001) but also in COPD (p=0.035) compared with healthy volunteers. Combining responses to all challenge agents suggested each individual challenge independently predicted the differences between disease groups and healthy volunteers (PGE2 p<0.001, CA p=0.018 and CAP p=0.015). Conclusions: Cough responses to inhalational cough challenges can discriminate healthy controls from airway diseases. Furthermore, cough challenge agents differ in their ability to distinguish health from disease implying different underlying mechanisms drive coughing in these diagnoses. A combination of cough challenge tests appears to be better at discriminating diagnostic groups compared with any individual test in isolation.